Technological and Institutional Innovations for Marginalized Smallholders in Agricultural Development - Gatzweiler, Franz W.; von Braun, Joachim (Springer Nature, 2016)
Agriculture; Agricultural Economics; Geography, general; Innovation/Technology Management